A better buy‐one‐give‐one business model. (14th July 2020) - Yen, Pi‐Ying; Chen, Ying‐Ju; He, Qiao‐Chu
Abstract: Buy‐one‐give‐one is a prevailing business model among social enterprises nowadays. Under this model, for every product sold, a social enterprise will donate the same or a similar product to a person in need. However, two questions arise: Should the social enterprise stick to donating the same product? Should the social enterprise stick to donating one product? In this paper, we explore different formats of buy‐one‐give‐one and compare buy‐one‐give‐one with cross‐subsidy with regard to social welfare, including both financial payoff and social payoff. The findings show that the social enterprise can generate more social welfare by differentiating its products into high‐end products for purchasers (the rich) and low‐end products for recipients (the poor) instead of providing these two segments products of the same quality. Also, giving more than just one product to the poor when one product is sold is an effective way to increase social welfare. We find that buy‐one‐give‐one results in higher social welfare than cross‐subsidy when either the social enterprise is highly socially responsible or the social gap between the rich and the poor is significant. However, when the size of the rich population is negligible, the buy‐one‐give‐one business model no longer pays. The social welfare under cross‐subsidy is at least the same as that under buy‐one‐give‐one in this case.